Razmah komercialnih genetskih in genomskih testiranj ter izzivi za medicinske sestre - Vrhovnik Mlekuž, Tjaša (Obzornik zdravstvene nege, 2025)
ntroduction: Recent developments in genetics and genomics have brought about new opportunities in medicine and nursing. Genetic testing, which underpins these clinical activities, has also emerged as a commercial, web-based service. The aim of this study was to identify the challenges that commercial genetic and genomic testing presents for nursing.Methods: A literature review was conducted using the PubMed/Medline, CINAHL Ultimate, and ScienceDirect databases with the following search terms: ‘direct-to-consumer’, ‘nursing’, ‘genetic counselling’ and their synonyms. The literature search yielded 12 papers, which were screened according to evidence strength.Results: Four main themes were identified: the experience of health professionals with direct-to-consumer genetic testing, informing nurses about direct-to-consumer genetic testing, discussions about nurses’ competencies in relation to direct-to-consumer genetic testing and concerns about the regulation of direct-to-consumer genetic testing.Discussion and conclusion: There is a very limited body of empirical research and scientific literature on direct-to-consumer genetic testing in relation to nursing. Addressing commercial genomic testing and genomics in general will require nurses to possess adequate knowledge and competencies. Further research is needed, which could include the use of validated questionnaires, the creation of prototype teaching content about commercial testing for nurses, and the utilisation of the Delphi method to identify expert opinions on the importance of educating various segments of the public regarding commercial genetic and genomic testing.
Keywords: elective genomics; elektivna genomika; genetic counselling; genetsko svetovanje; genomic literacy; genomska pismenost; nursing; zdravstvena nega